The Influence of Brand Ambassador BTS (Bangtan Seoyeondan) on Tokopedia Consumer Purchase Intention in Bandung City - Natalie Christina Rahayu; Nuslih Jamiat (Udayana Journal of Social Sciences and Humanities, 2021)
This study aims to determine the influence of BTS brand ambassador (bangtan seoyeondan) on purchase intention of Tokopedia consumers in Bandung City. This study aims to find out and analyze the reaction of Tokopedia consumers to BTS as the Tokopedia brand ambassador in Bandung, and the reaction of Tokopedia consumers to the purchase intentiom of Tokopedia consumers in Bandung, and how much their influence as a brand has on BTS . Meet the buying interest of Tokopedia consumers. In Bandung City. The method used in this study is a quantitative method that describes the type of related research. The sampling used in this study is a non-probabilistic type of intentional sampling, with a maximum of 100 respondents. The data analysis techniques used in this study are descriptive analysis and simple linear regression analysis. Based on the results of part of the hypothesis test (ttest), it is found that the brand ambassador variable has a significant negative impact on the purchase intention of Tokopedia consumers in Bandung.